Longitudinal Trends of Comorbidities and Survival Among Kidney Cancer Patients in Asian Population - Jung, Minji; Choo, Eunjung; Li, Jinhui; Deng, Zhengyi; Langston, Marvin E.; Lee, Sukhyang; Chung, Benjamin I. (Cancer Medicine, 2024)
Background: Comorbidity could influence cancer diagnosis, treatment, prognosis, or survival. Although comorbidity burden in kidney cancer patients is high, limited evidence exists on the longitudinal patterns of individual comorbidity prevalence and its impact on overall survival among kidney cancer patients, particularly in Asian populations. Methods: We included adults diagnosed with kidney cancer between 2010 and 2021 using the Korean nationwide health insurance database. Comorbidities assessed were any 1 of 19 specific medical conditions, diagnosed within 1 year prior to cancer diagnosis. We calculated the incidence and age-standardized incidence rate of kidney cancer, prevalence of individual medical conditions as single or multiple comorbidities, and overall survival probability of kidney cancer patients over a 12-year period. We estimated the odds ratio (OR) of having individual and multiple comorbidities with age and sex as independent covariates and adjusted for other comorbidities. Kaplan–Meier curves were used for overall survival at different time frames up to 5 years of follow-up. Results: Among kidney cancer patients (N = 42,740), 68.7% were men, and median (interquartile range) age was 59 (49–68) years. Approximately 76% of patients had at least one comorbidity at the time of cancer diagnosis. Overall, hypertension (51.3%), dyslipidemia (40.2%), mild liver disease (27.4%), diabetes (25.1%), and peptic ulcer disease (18.9%) were the most prevalent comorbidities. The proportion of patients having three or more comorbidities continuously increased from 2010 (29.4%) to 2021 (44.9%). Having more comorbidities was associated with a lower probability of overall survival. Conclusion: Comorbidities were prevalent in kidney cancer patients, and the proportions of patients with multiple conditions increased over time. Although survival probability increased over time, it was attenuated by having more comorbidities. Our data emphasizes the importance of comprehensive management for both cancer and comorbid conditions in kidney cancer patients.
Keywords: Adult; Aged; Asian People; Comorbidity; Female; Humans; Incidence; Kidney Neoplasms; Longitudinal Studies; Male; Middle Aged; Prevalence; Republic of Korea; comorbidity; kidney cancer; survivorship